(3dhGeY GdfXQ aj JMbjb eYGfi GdeNJUQs - (3CMeO Hf eMeO Hf eMeO Hf jYbhH GdhGdis; (3LdGd GdOjf GdeMdj , LdGd GdOjf GdSjhWjs
(3ChdgG (B:s
(3hHYO adeG cGf Yde hjHdZ Hg Yde GdMbGFb hjJUa HMbGFb GdYdhe s
(3BNQgG (B:s
(3hgPG fgGjI eG CQOfG EjQGOg ai gPG GdTQM GdeHGQc s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B333 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B311s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B_ (3GdeZQH (B(254) s
Keywords: (3GdadSaI hGdefWbs